Advanced glycation end products and their ratio to soluble receptor are associated with limitations in physical functioning only in women: results from the CARLA cohort - Ebert, Helen; Lacruz, Maria Elena; Kluttig, Alexander; Simm, Andreas; Greiser, Karin Halina; Tiller, Daniel; Kartschmit, Nadja; Mikolajczyk, Rafael (BMC geriatrics, 2019)
Advanced glycosylation, Physical function, Biomarker, Disability